Charging electric cars as a way to increase the use of energy produced from RES - Małek Arkadiusz; Caban Jacek; Wojciechowski Łukasz (Open Engineering, 2020)
The article contains an analysis of charging electric cars as a way to increase the use of energy produced from a photovoltaic system. A photovoltaic system is described, consisting of two micro installations, with a power output of up to 40 kWp each, supplying two sectors of the building of the Lublin Science and Technology Park. An internet platform for monitoring the operation of a photovoltaic system is presented. Next, an innovative system for monitoring, consumption and production analysis of electric energy in individual building sectors is described. A surplus of energy produced in one of the sectors was found. It was proposed that this excess energy would be used to charge electric vehicles. An analysis of the surplus power generated by the photovoltaic system in excess of the energy consumed by the building sector was used to determine the power available to the wall charger. The surplus of energy produced was used for calculations related to the amount of charging the electric vehicle required and the cost of traveling 100 km. Charging an electric car not only provides a faster return on investment in the installation, but also presents drivers with a very ecological and economical transport solution.